Non-invasive taxonomic identification of fish species by using scanning electron microscopy: A comparative study of scale microstructures among the Hypophthalmichthys molitrix and Otolithes ruber - Inayat, Arfia; Masood, Zubia; Ahmed, Quratulan; Said, Mourad Ben; Kabir, Muhammad; Yousaf, Muhammad; Ríos-Escalante, Patricio R De los; Ali, Wajid (Journal of Advanced Veterinary and Animal Research, 2025)
Objectives: Recent studies on teleost fish evolution compare both molecular and morphological data to evaluate the taxonomic relationships. Therefore, the objective of our current study was to assess the potential of using scale microstructures for the taxonomic identification of two fish species, i.e., Hypophthalmichthys molitrix and Otolithes ruber. Materials and Methods: Eighty individuals of each carp species were collected from the Quetta fish market between August 2021 and January 2022. Then, microstructures, i.e., scale length and width, focus position, and the number of radii and ctenii of each fish scale obtained from five different fish-body regions, were examined. These measurements were used to compare the variations in scale microstructures between two fish species and may also help evaluate their potential utility in more accurate species identification and systematic classification. Results: The overall results reveal statistically significant variations (p < 0.05) between all examined scale microstructures, including the length or width of the scale, the focus position, and the number of radii or ctenii present on the fish scale, obtained from five body regions of two carp fish species. These results exhibit the potential utility of microstructure studies as a reliable approach for systematic identification. Therefore, our findings support the usage of fish scale microstructures as a valuable and non-invasive tool for taxonomic identification of any fish species. Moreover, this technique may specify the actual impact of these scale features as valuable tools for the conservation and management of endangered or threatened fish species. Conclusion: Our study provides a foundation for future systematic research and offers a satisfactory approach for non-invasive taxonomic identification. J. Adv. Vet. Anim. Res., 12(3): 806–816, September 2025 http://doi.org/10.5455/javar.2025.l943